Unilateral action by the EC against unfair trade practices - Harald Großmann (Intereconomics, 1993)
The European Community has a variety of instruments at its disposal to counter unfair trade practices, but there has long been considerable disagreement within the Community as to when and where they should be applied. To what extent would such measures endanger the benefits of international trade? Can any positive effects be expected?
Keywords: 330; European Community